Comprehensive Physiology 2013
DOI: 10.1002/cphy.c120008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal Function; Clearance, the Renal Microcirculation, Renal Blood Flow, and Metabolic Balance

Abstract: Historically, tools to assess renal function have been developed to investigate the physiology of the kidney in an experimental setting, and certain of these techniques have utility in evaluating renal function in the clinical setting. The following work will survey a spectrum of these tools, their applications and limitations in four general sections. The first is clearance, including evaluation of exogenous and endogenous markers for determining glomerular filtration rate, the adaptation of estimated glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 215 publications
1
35
0
Order By: Relevance
“…Here we show that Rap1b in kidney does not have a major function in that process, as we have observed normal gross kidney histology and no major changes in indices of renal function or plasma renin activity in Rap1b −/− mice. However, a number of additional studies would need to be performed to fully understand the role of Rap1b in kidney function 43 and in regulation of tissue renin-angiotensin system, which also contributes to BP regulation. Likewise, it is conceivable that Rap1b in the sympathetic nervous system contributes to the regulation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that Rap1b in kidney does not have a major function in that process, as we have observed normal gross kidney histology and no major changes in indices of renal function or plasma renin activity in Rap1b −/− mice. However, a number of additional studies would need to be performed to fully understand the role of Rap1b in kidney function 43 and in regulation of tissue renin-angiotensin system, which also contributes to BP regulation. Likewise, it is conceivable that Rap1b in the sympathetic nervous system contributes to the regulation of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma endogenous creatinine concentration is commonly used to estimate the GFR, but it may result in erroneous estimates due to age, gender, muscle mass and many other anthropometric variables. 3 Determination of the plasma/urinary clearance of exogenous renal markers (such as 99m Tc-DTPA, inulin and iothalamate) is invasive and cumbersome, due to the requirement of multiple blood/urine sampling steps and tedious sample analysis by HPLC. 4 Moreover, many studies revealed that creatinine and iothalamate are secreted by proximal tubule cells, while cystatin C and 99m Tc-DTPA are reabsorbed by the tubular epithelial cells, leading to a bias in the GFR.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Therefore, monitoring limited to global evaluation of renal blood flow tells very little about the adequacy of oxygen supply to the kidneys. [17] As a consequence, renal Doppler is not a reliable tool to assess oxygen supply and its potential response to fluid loading.…”
Section: Renal Dopplermentioning
confidence: 99%